Cardiac resynchronization therapy in the elderly: A realistic option for an increasing population? - António, N (2011)
Cardiac resynchronization therapy (CRT) has become a mainstay of heart failure treatment. Since heart failure is a disease primarily affecting older patients it is important to evaluate the performance of CRT in this population. Elderly has been suggested as a subgroup less likely to benefit from CRT. This is an important issue that should be clarified, because most patients with heart failure are old. The present review discusses the available data concerning cardiac resynchronization therapy in the elderly, focusing on efficacy, indication, safety, and impact of co-morbidities